The Effect of Schedule, Rate and Passenger Complaints on Consumer Decisions Using the Bus Fleet of PT. ALS (Introduction to Sumatra) - Irwansyah; Suhaila Husna Samosir (International Journal of Economics (IJEC), 2022)
This study aims to analyze the effect of schedules, fares and passenger complaints on consumer decisions to use the PT. ALS. The method used in this research is quantitative. The population in this study is ALS bus passengers with a total of 11,655 people using the ALS bus fleet for the last 3 months starting from December 2021 - February 2022. In this study, samples were taken using the Slovin formula, and using a probability sampling technique, namely proportionate stratified random sampling. The total number of respondents in this study were 101 consumers. The analytical method used is multiple linear regression method using SPSS Version 25.00 program. The results obtained from the coefficient value of 0.293, where the value of t-count > t-table (3.637 > 1.6602) and a significant value of 0.000 is smaller than 0.05, meaning that the schedule has a significant effect on consumer decisions, then Ha1 is accepted. The calculated F value is 70.779. With = 5%, dk of numerator: 4, dk of denominator: 101-3-1 (5%; 2; 97; Ftable 2.47) obtained F table value of 2.47. From this description it can be seen that F arithmetic (70,779) > F table (3,15), and a significance value of 0.000 <0.05, it can be concluded that the third hypothesis is accepted, meaning that the Schedule Variable (X1 ) , Tariff ( X2 ) and Passenger Complaints (X 3 ) have a simultaneous (simultaneous) effect on the Consumer Decision Variable (Y).